Research Analysis of Built Environment as a System: Implementing Research Through Design Methodology - Suberi, Hari Kumar (Frontiers in Built Environment, 2022)
Building is a process of technology that enables human wellbeing by engaging a multitude of stakeholders. However, it is often seen in the literature that all stakeholders involved in the building process are disintegrated, which seems to be a management and systemic orientation problem when trying to address the built environment as a sustainable system design. That means the design and design aesthetics of any building cannot be simply influenced by technological revolution and efficiency improvements to attain the three pillars of sustainable development. A systemic transformation of the whole process is a pre-requisite, which is complex and oft underestimated mainly due to the lack of subjective characteristics involved available for transformation research, that addresses policy choice in the development of a paradigm shift. Addressing built environment as a system for transformation research practice, this study extensively reviewed the UNEP built environment report to identify global variables that define the roughly correct system as an artifact to be studied. The UNEP report covers the system level transformation requirement until 2003, which seems to be more or less the same in almost all the research studies as of now. Using the Vester Sensitivity Model, the roughly correct built environment as a system is analyzed to identify the future leverage potential and variables’ interdependency. The in-depth systems analysis indicates global variables Enabling condition and New material are potential system leveraging variables for built environment system transition to sustainable design, which require further scrutiny. The leveraging variables are influenced by other global variables which can only be negotiated for sustainable development goal actualization for future success.